The Use of Intranasal Dexmedetomidine and Midazolam for Sedated Magnetic Resonance Imaging in Children: A Report From the Pediatric Sedation Research Consortium. Issue 3 (March 2020) - Sulton, Carmen; Kamat, Pradip; Mallory, Michael; Reynolds, Jason
Abstract : Objective: The objective of this study was to describe the use of intranasal dexmedetomidine (IN DEX) for sedated magnetic resonance imaging (MRI) examinations in children. The use of IN DEX for MRI in children has not been well described in the literature. Materials and Methods: The Pediatric Sedation Research Consortium (PSRC) is a collaborative and multidisciplinary group of sedation practitioners dedicated to understanding and improving the process of pediatric sedation. We searched the 2007 version of the PSRC database solely for instances in which IN DEX was used for MRI diagnostic studies. Patients receiving intravenous medications were excluded. Patient demographics, IN DEX dose, adjunct medications and dose, as well as procedure completion, complications, interventions, and monitoring providers were analyzed. Results: A total of 224 sedation encounters were included in our primary analysis. There were no major adverse events. Most sedations (88%) required no intervention. Registered nurses were the monitoring provider in over 99% of cases. The median (interquartile range) dose of dexmedetomidine was 3 (2.5–3) mcg/kg. Adjunctive midazolam was used in 219/224 (98%) of the cases. All procedures were completed. Conclusions: This report from the PSRC shows that IN DEX in combination with midazolam is an effective medication regimen for children who require an MRI with sedation.